Model Persediaan pada Produk yang Mendekati Masa Kadaluwarsa: Mempertimbangkan Diskon Penjualan dan Retur - Laila Nafisah; Wellem Sally; Puryani Puryani (Institute of Research and Community Outreach - Petra Christian University, 2016)
Most products are sold in Mirota Campus Supermarkets have perishable nature. One of the strategies undertaken in product sales is by providing discounts on products approaching expiry date. The closer to the expiration date, then the discounts given per unit will increase. Allows product pemasoks can in returns with the terms and conditions agreed. In this paper, developed a model multi-item inventory for a product that has a shelf-life of taking into account discounts and product returns. Completion of the model is done with optimization approach based on parameters that influence in this model. Numerical examples are given at the end of this paper to illustrate the model settlement algorithms.